Decision analysis in the management of duodenal adenomatosis in familial adenomatous polyposis. Issue 6 (June 1997) - Vasen, H F; Bülow, S; Myrhøj, T; Mathus-Vliegen, L; Griffioen, G; Buskens, E; Taal, B G; Nagengast, F; Slors, J F; de Ruiter, P
Abstract : BACKGROUND: Patients with familial adenomatous polyposis are not only at high risk of developing adenomas in the colorectum but a substantial number of patients also develop polyps in the duodenum. Because treatment of duodenal polyps is extremely difficult and it is unknown how many patients ultimately develop duodenal cancer, the value of surveillance of the upper digestive tract is uncertain. AIMS: (1) To assess the cumulative risk of duodenal cancer in a large series of polyposis patients. (2) To develop a decision model to establish whether surveillance would lead to increased life expectancy. METHODS: Risk analysis was performed in 155 Dutch polyposis families including 601 polyposis patients, and 142 Danish families including 376 patients. Observation time was from birth until date of last contact, death, diagnosis of duodenal cancer, or closing date of the study. RESULTS: Seven Dutch and five Danish patients developed duodenal cancer. The lifetime risk of developing this cancer by the age of 70 was 4% (95% confidence interval 1-7%) in the Dutch series and 3% (95% confidence interval 0-6%) in the Danish series. Decision analysis showed that surveillance led to an increase in life expectancy by seven months. CONCLUSIONS: Surveillance of the upper digestive tract led to a moderate gain in life expectancy. Future studies should evaluate whether this increase in life expectancy outweighs the morbidity of endoscopic examination and proximal pancreaticoduodenectomy.